Molecular docking and dynamics study of natural compound for potential inhibition of main protease of SARS-CoV-2. Issue 16 (2nd November 2021) - Mahmud, Shafi; Uddin, Mohammad Abu Raihan; Zaman, Meemtaheena; Sujon, Khaled Mahmud; Rahman, Md. Ekhtiar; Shehab, Mobasshir Noor; Islam, Ariful; Alom, Md. Wasim; Amin, Al; Akash, Al Shahriar; Saleh, Md. Abu
Abstract: Newly emerged SARS-CoV-2 made recent pandemic situations across the globe is accountable for countless unwanted death and insufferable panic associated with co-morbidities among mass people. The scarcity of appropriate medical treatment and no effective vaccine or medicine against SARS-CoV-2 has turned the situation worst. Therefore, in this study, we made a deep literature review to enlist plant-derived natural compounds and considered their binding mechanism with the main protease of SARS-CoV-2 through combinatorial bioinformatics approaches. Among all, a total of 14 compounds were filtered where Carinol, Albanin, Myricetin were had better binding profile than the rest of the compounds with having binding energy of –8.476, –8.036, –8.439 kcal/mol, respectively. Furthermore, MM-GBSA calculations were also considered in this selection process to support docking studies. Besides, 100 ns molecular dynamics simulation endorsed the rigid nature, less conformational variation and binding stiffness. As this study, represents a perfect model for SARS-CoV-2 main protease inhibition through bioinformatics study, these potential drug candidates may assist the researchers to find a superior and effective solution against COVID-19 after future experiments. Communicated by Ramaswamy Sarma